La Conversation des sexes: philosophie du consentement - Garcia, Manon (Climats, 2021)
« L'affaire Weinstein et le mouvement #MeToo ont mis la question des violences sexuelles au premier plan. Depuis, le consentement renvoie naturellement au consentement sexuel et amoureux, envisagé comme un sésame de l'égalité entre femmes et hommes. Pourtant, il est bien difficile à définir, et soulève trois problèmes. Le problème juridique, bien connu de celles et ceux qui suivent l'actualité, peut être résumé ainsi : que faire pour que les cas de viol, d'agression et de harcèlement sexuels soient efficacement punis? Le deuxième problème est moral : comment penser des relations amoureuses et sexuelles qui ne soient pas fondées sur des normes sociales sexistes et inégalitaires? Enfin, le problème politique : comment ne pas reconduire les injustices de genre qui se manifestent dans les rapports amoureux et sexuels? La magistrale analyse du consentement que propose Manon Garcia revisite notre héritage philosophique, plongeant au cœur de la tradition libérale, mettant à nu ses impensés et ses limites. De John Locke aux théoriciennes féministes françaises et américaines, en passant par Michel Foucault et les débats sur la pratique du BDSM, c'est une nouvelle cartographie politique de nos vies privées que dessine cet essai novateur. Au terme de ce livre, il s'agira en somme, pour reprendre la formule de Gloria Steinem, d'« érotiser l'égalité » plutôt que la domination : en ce sens, le consentement sexuel, conçu comme conversation érotique, est sans doute l'avenir de l'amour et du sexe. »
Section: 308 pages ; 21 cm
Keywords: 2000 à aujourd'hui; approches et analyses; consentement; cours; discipline; droits des femmes*; europe; france; féminisme pop; justice sociale; metoo; phi4336; philosophie; premier cycle; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; thématiques

Rethinking the effects paradigm in porn studies - McNair, Brian (Porn Studies, 2014)
It has been an assumption of most anti-pornography discourse that porn damages women (and children) in a variety of ways. In Porno? Chic!, the author interrogated this assumption by examining the correlation between the incidence of sexual violence and other indicators of misogyny, and the availability and accessibility of pornography within a number of societies. This article develops that work with a specific focus on the regulatory environment as it relates to pornography and sexual representation. Does a liberal regulatory regime in sexual culture correlate with a relatively advanced state of sexual politics in a given country? Conversely, does an illiberal regime, where pornography and other forms of sexual culture are banned or severely restricted, correlate with relatively strong patriarchal structures? A comparative cross-country analysis seeks to explain the correlations identified, and to assess the extent to which the availability of porn can be viewed as a causal or a consequential characteristic of those societies where feminism has achieved significant advances.
Keywords: LGBTQIA2+; analyse comparée; approches et analyses; communication; corps; cours; discipline; droits des femmes*; féminisme pop; histoire et politique; identités LGBTQIA2+; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; violences; études culturelles

Porno? Chic!: how pornography changed the world and made it a better place - McNair, Brian (Routledge, 2013)
Porno? Chic! examines the relationship between the proliferation of pornography and sexualised culture in the West and social and cultural trends which have advanced the rights of women and homosexuals. Brian McNair addresses this relationship with an analysis of trends in sexualised culture since 2002 linked to a transnational analysis of change in sexual politics and sex/gender relations in a range of societies, from the sexually liberalised societies of advanced capitalism to those in which women and homosexuals remain tightly controlled by authoritarian, patriarchal regimes. In this accessible, jargon-free book, Brian McNair examines why those societies in which sexualised culture is the most liberalised and pervasive are also those in which the socio-economic and political rights of women and homosexuals have advanced the most.
Section: xii, 188 p. : ill. ; 24 cm
Keywords: LGBTQIA2+; approches et analyses; communication; cours; discipline; droits des femmes*; féminisme pop; identités LGBTQIA2+; justice sociale; premier cycle; queer; sciences humaines; sciences sociales; sex1911; sexualité; thématiques; études culturelles